Elites, Institutions and the Quality of Government
XIX, 311 p.
Keywords: To a large extent, elite politicians, bureaucrats, and businessmen hold the fortunes of their societies in their hands. This edited volume describes how formal and informal institutions affect elite behaviour, which in turn affects corruption and the quality of government.